Antimicrobial activities and phytochemical screening of leaf extract of Mikania micrantha H.B.K - Devkota, Anjana; Sahu, Anita (Journal of Natural History Museum, 2018)
Antimicrobial activities and phytochemical screening of leaves of Mikania micrantha was tested in laboratory against phytopathogenic fungi and human pathogenic bacteria. The leaves samples were extracted in distilled water and methanol. The crude extracts of leaves were assessed in-vitro for antimicrobial activity using different concentrations (50, 100, 150,200, and 250 mg/ml) against five fungal strains (viz. Sclerotium rolfsii, Phytopthora capsici, Alternaria brassicae, Fusarium oxysporum and Botrytis cinerea) and six bacterial strains (Klebsiella pneumoniae, Proteus mirabilis, Escherichia coli, Bacillus subtilis, Enterococcusfaecalis and Staphylococcus aureus). Antifungal activity was tested by Poison Food Technique and Linear Mycelium growth Reduction (LMGR) percentage was determined. In crude extractof M. micrantha, the highest LMGR percentage was found in F. oxysporum in both distilledwater and methanol extract. Antibacterial activity was carried out by Disc Diffusion method. In the crude leaf extract of M. micrantha Gram negative bacteria was found more resistant than Gram positive bacteria. Methanol extract was found more effective in determining the Zone of Inhibition for all the strains of bacteria in all the concentrations. The plant extracts were found more effective in showing antibacterial activity than antifungal activity. The phytochemicalscreening revealed that the selected species contained tannin, saponins, alkaloid, flavonoid, cardiac glycosides and terpenoids. This result supports the potential of this plant species used as a new chemotherapeutic drug.